DBC ceramic copper-clad plate and preparation process thereof
By adopting sandwich structure and modified nanographene technology of high-thermal stability thermally conductive copper plate and CuO plated transition layer in the ceramic copper clad process, the problems of complex and high cost of ceramic copper clad plate are solved, and high peel strength and thermal conductivity are achieved and improve thermal stability.
Patent Information
- Application Number
- CN202411410840.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In the existing ceramic copper clad preparation process, active elements Ti and Cr are difficult to be corroded, resulting in complex and high cost. When the active elements are not added, the bonding ability of the conductive Cu layer to the ceramic substrate is reduced, affecting thermal stability and peel strength.
Using a sandwich structure of high-thermal stability thermally conductive copper plate and a ceramic substrate plated with CuO transition layer, the CuO transition layer is deposited by pulsed laser and oxygen plasma is introduced, and the nano-copper layer is grown in combination with modified nanographene and NaBH4 solutions to enhance the attachment of CuO film. Focus and density, reduce defects, improve thermal conductivity and peel strength.
The high peel strength, excellent thermal conductivity and thermal stability of DBC ceramic copper clad plate is achieved, which simplifies the etching process, reduces costs, and improves the overall performance of ceramic copper clad plate.
Smart Images

Figure CN119233549A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic packaging, in particular to a DBC ceramic copper-clad plate and a preparation process thereof. Background Art
[0002] DBC (Direct Bonded Copper) ceramic copper clad laminate is an advanced composite material widely used in high-power electronic equipment, power modules, LED substrates and automotive electronics. DBC ceramic copper clad laminate attaches a copper layer to a ceramic substrate, combining the high thermal conductivity and electrical insulation of ceramic materials with the high conductivity and high mechanical strength of copper. It has excellent thermal performance and mechanical stability and is suitable for harsh working environments.
[0003] Currently, the most commonly used method for preparing ceramic copper-clad laminates is the active metal brazing method, which usually involves adding active elements such as Ti, Zr and Cr to the alloy solder, and then plating them on the ceramic surface as a transition layer. Although this method can improve the bonding strength between the ceramic substrate and the conductive Cu layer, when wet etching the circuit, Ti and Cr are difficult to be corroded by general corrosive solutions and only react with strong acids and strong alkalis. Multiple etching processes are required when preparing the circuit, and the process is too complicated and costly. However, if no active elements are added to the alloy solder, the bonding ability between the conductive Cu layer and the ceramic substrate will be greatly reduced, and the thermal stability and peel strength of the ceramic copper-clad laminate will be reduced. Summary of the invention
[0004] In order to solve the above technical defects, the present invention has developed a DBC ceramic copper clad laminate with high peel strength, strong thermal conductivity, excellent thermal stability and easy etching, and a preparation method thereof.
[0005] A preparation process of a DBC ceramic copper-clad laminate comprises the following steps: S1: Preparation of high thermal stability thermal conductive copper plate The nanographene is immersed in a fluorotitanic acid solution for ultrasonic treatment, and then immersed in a 2-hydroxyethylenediaminetetraacetic acid solution, triethoxysilane is added, and the temperature is increased and magnetic stirring is performed, and the modified nanographene is obtained by filtration and drying, NaBH4 and ethanol solution are mixed and placed in an ice-water bath for ultrasonic treatment to obtain a NaBH4 solution, CuCl2, the modified nanographene and the ethanol solution are evenly mixed, and nitrogen is continuously introduced after polyvinyl pyrrolidone is added, and then the solution is placed in an ice-water bath for ultrasonic treatment, and the container is sealed and the NaBH4 solution is added dropwise while stirring, and the container is allowed to stand in an ice-water bath, and centrifugation, filtration and washing are repeated, and finally drying is obtained to obtain copper-coated graphene nanoparticles, and the copper-coated graphene nanoparticles are mixed with oxygen-free pure copper powder for cold isostatic pressing, and graphene-copper ingots are obtained after sintering, and then horizontal continuous casting, annealing, milling to remove the oxide layer, rolling and degreasing and cleaning are performed in sequence to obtain a high thermal stability thermal conductive copper plate; S2: Pulsed laser deposition of CuO transition layer on ceramic substrate The copper acetate and ethanol solution are mixed and placed in a container, the pH value of the solution is adjusted and the sealed container is shaken, after filtering, it is washed with deionized water and anhydrous ethanol in sequence, and dried to obtain CuO nanoparticles, after rinsing the ceramic substrate with deionized water, it is immersed in acetone solution, hydrofluoric acid solution and deionized water in sequence for ultrasonic cleaning, and dried to obtain a clean ceramic substrate, the clean ceramic substrate is used as a substrate, and the CuO nanoparticles are used as a target material and placed in a deposition chamber of a pulsed laser deposition system for deposition coating, and oxygen plasma is introduced into the deposition chamber through a heated electric heating nozzle while the coating is being deposited, so as to obtain a CuO transition layer-coated ceramic substrate; S3: Composite of high thermal stability thermal conductive copper plate and CuO transition layer ceramic substrate The copper clad laminate is assembled in a sandwich structure of a high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate, and is clamped by a quartz plate to obtain a pre-assembled copper clad laminate. The pre-assembled copper clad laminate is placed in a vacuum furnace for brazing, the vacuum degree in the vacuum furnace is adjusted, and then two-stage temperature rising brazing is performed. After cooling, a DBC ceramic copper clad laminate is obtained.
[0006] Furthermore, step S1 of preparing a thermally conductive copper plate with high thermal stability comprises the following steps: S1.1: immerse 2-3 portions of nanographene in a 60-70% fluorotitanic acid solution, then perform ultrasonic treatment for 8-10 minutes at a frequency of 25-30kHz using an ultrasonic generator, then immerse in a 0.1-0.2 mol / L 2-hydroxyethylenediaminetetraacetic acid solution, add 10-15wt% triethoxysilane, heat to 45-60°C, then perform magnetic stirring for 3-4 hours, filter and dry to obtain modified nanographene; S1.2: NaBH4 and ethanol solution were mixed in a mass ratio of 1: (45-50) and placed in an ice water bath at 0-4°C, and then ultrasonicated for 10-15 minutes using an ultrasonic generator to obtain a NaBH4 solution. CuCl2, modified nanographene and ethanol solution were mixed in a mass ratio of 1: (0.8-1.2): (60-80) and placed in a container. 0.5-0.8wt% polyvinyl pyrrolidone was added and nitrogen was continuously introduced for 10-15 minutes, and then placed in an ice water bath at 0-4°C and ultrasonicated for 10-15 minutes. minutes, dripping 25-30wt% NaBH4 solution through a catheter in a sealed container, stirring rapidly while dripping, and after the NaBH4 solution is dripped, continue to stand in an ice water bath at 0-4°C for 45-50 minutes, and then centrifuge at a speed of 10000-12000rpm for 5-6 minutes, and then immerse in an ethanol solution and stir for 6-8 minutes after filtering, and then centrifuge and filter again, repeat 2-3 times, and then place in a drying oven at a temperature of 60-65°C for 4-6 hours to obtain copper-coated graphene nanoparticles; S1.3: The copper-coated graphene nanoparticles and oxygen-free pure copper powder are mixed evenly in a mass ratio of 1: (10-12), loaded into a mold, and pressed into shape by cold isostatic pressing at 300-500Mpa. The mixture is then placed in a vacuum sintering furnace for sintering to obtain a graphene-copper ingot. The ingot is then subjected to horizontal continuous casting, annealing, milling to remove the oxide layer, rolling, and degreasing and cleaning to obtain a thermally conductive copper plate with high thermal stability.
[0007] Further, step S2, pulse laser deposition of a CuO transition layer on a ceramic substrate, comprises the following steps: S2.1: copper acetate and ethanol solution are mixed in a container at a mass ratio of 1: (40-50), the pH of the solution is adjusted to 10-12, and then the sealed container is shaken for 20-30 minutes, filtered, washed with deionized water and anhydrous ethanol 2-3 times in sequence, and then placed in a vacuum drying oven at a temperature of 60-65°C for 6-8 hours to obtain CuO nanoparticles; S2.2: Rinse the ceramic substrate with deionized water for 2-3 times, then immerse it in an acetone solution for ultrasonic cleaning for 15-20 minutes, then immerse it in a 5-6% hydrofluoric acid solution for ultrasonic cleaning for 5-6 minutes, then immerse it in deionized water for ultrasonic cleaning for 8-10 minutes, then put it in a drying oven, adjust the temperature to 100-120°C and dry it for 10-15 minutes to obtain a clean ceramic substrate; S2.3: Oxygen is introduced into the gas chamber of the RF plasma generator. The gas chamber is equipped with an electrothermal nozzle, which is connected to the deposition chamber of the pulsed laser deposition system. First, the electrothermal nozzle valve is closed, and the RF plasma generator power is set to 300-500W and the RF frequency is set to 13-14MHz. At the same time, a clean ceramic substrate is used as a substrate, and CuO nanoparticles with a purity of more than 99% are used as a target material. The distance between the substrate and the target material is adjusted to 6-8cm, and the pressure of the deposition chamber is pre-pumped to 1×10 -4 -2×10 -4 Pa and set the laser parameters to 180-200mJ / Plus and the laser density to 4-5J / cm 2 First, turn on the plasma generator to continuously generate oxygen plasma, then heat the electric heating nozzle to 400-450°C, the deposition chamber temperature to 500-550°C, then open the electric heating nozzle valve, control the oxygen plasma flow rate to 15-20sccm, control the deposition frequency of the pulsed laser deposition system to 5-6Hz, and control the thickness of the deposited CuO film to 50-100μm to obtain a CuO transition layer-coated ceramic substrate.
[0008] Furthermore, step S3 of compounding the high thermal stability thermal conductive copper plate with the CuO transition layer plated ceramic substrate comprises the following steps: S3.1: The copper clad laminate is assembled in a sandwich structure of high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate. Quartz plates are used to clamp the upper and lower parts, and the pressure is adjusted to 5×10 -3 -7×10 - 3 MPa, and a pre-assembled copper clad laminate is obtained; S3.2: Place the pre-assembled copper clad laminate in a vacuum furnace for brazing, and adjust the vacuum degree in the vacuum furnace to 10 -4 -5×10 -4 Pa, then heat it to 800-850°C at a heating rate of 5-6°C / min, keep it warm for 25-30 minutes, then heat it to 920-950°C at a heating rate of 2-3°C / min, and then cool it to room temperature with the furnace to obtain a DBC ceramic copper clad laminate.
[0009] Furthermore, the ethanol solution in step S1.2 is a mixture of ethanol and deionized water, wherein the volume fraction of ethanol is 50-60%.
[0010] Furthermore, in step S1.2, the gas flow rate of nitrogen is 40-45 mL / min.
[0011] Furthermore, the thickness of the high thermal stability thermal conductive copper plate prepared in step S1.3 is 0.5-1 mm.
[0012] Furthermore, in step S2.1, the pH value is adjusted to 10-12 by adding sodium hydroxide dropwise while stirring.
[0013] Furthermore, in step S2.2, the material of the ceramic substrate is Si3N4 ceramic.
[0014] A DBC ceramic copper-clad plate is prepared by the preparation process of the DBC ceramic copper-clad plate.
[0015] The beneficial effects are as follows: 1. The present invention introduces oxygen plasma during the process of CuO pulse laser deposition coating on a clean ceramic substrate. First, pure CuO is used to avoid the introduction of active elements such as Ti and Cr in the traditional process, so that the subsequently prepared DBC ceramic copper-clad laminate can be easily etched. Secondly, oxygen plasma is introduced into the deposition chamber, and CuO nanoparticles can collide and contact with the oxygen plasma at high speed during the deposition process, which can not only effectively remove organic impurities on the surface of the CuO nanoparticles, enhance their surface activity, reduce the wetting angle between non-oxide ceramics and metals and improve adhesion, but also the high energy of the oxygen plasma can promote the surface rearrangement and crystallization of the CuO nanoparticles to form a more ordered crystal structure, thereby greatly reducing defects and voids in the CuO film, forming a uniform and compact CuO film, so that the prepared CuO-plated transition layer ceramic substrate can be better combined with the high thermal stability thermal conductive copper plate, thereby improving the peeling strength and thermal conductivity of the DBC ceramic copper-clad laminate.
[0016] 2. The present invention first prepares a NaBH4 solution with strong reducing properties, then mixes the modified nanographene, CuCl2 and ethanol solution, adds polyvinyl pyrrolidone, passes nitrogen gas into the solution to remove oxygen, and then drops a reducing agent NaBH4 solution to reduce CuCl2 in the solution. 2+ Rapid reduction is carried out to grow a nano-copper layer on the surface of the modified nano-graphene. The nano-copper layer prepared by this method has excellent adhesion on the surface of the modified nano-graphene, and can greatly improve the interface compatibility between the copper-clad graphene nanoparticles and the oxygen-free pure copper powder. At the same time, after the nano-copper layer is grown, polyvinyl pyrrolidone can quickly coat the formed copper-clad graphene nanoparticles to prevent their continued growth and prevent the synthesized copper-clad graphene nanoparticles from being too large and causing a decrease in binding force. In summary, the various components in the high thermal stability thermal conductive copper plate can be tightly combined, which improves the thermal conductivity of the subsequent DBC ceramic copper-clad plate, and graphene has a lower thermal expansion coefficient. In summary, the risk of cracking and peeling of the copper layer at high temperature is effectively reduced, so that the DBC ceramic copper-clad plate can maintain good peeling strength after thermal cycling and has excellent thermal stability.
[0017] 3. The present invention immerses nanographene in a fluorotitanic acid solution for ultrasonic treatment, and the fluorotitanic acid reacts chemically with the surface of the nanographene to introduce fluorine-containing and titanium-containing functional groups on the graphene surface, thereby providing multiple active sites on the graphene surface and improving its chemical activity. The graphene surface is then treated with a 2-hydroxyethylenediaminetetraacetic acid solution and triethoxysilane, and the resulting modified nanographene can better bind Cu 2+ Adsorption is carried out to enable the subsequent modified nano-graphene surface to better grow a uniform and dense nano-copper layer, improve the bonding ability of copper-clad graphene nanoparticles and oxygen-free pure copper powder, and thus enhance the thermal stability of DBC ceramic copper-clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a process flow chart of the preparation of the DBC ceramic copper clad laminate used in the embodiments of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1 A DBC ceramic copper clad plate and its preparation process, such as Figure 1 As shown, the following steps are included: S1: Preparation of high thermal stability thermal conductive copper plate S1.1: 2 portions of nanographene were immersed in a 60% fluorotitanic acid solution, and then ultrasonicated for 8 minutes using an ultrasonic generator at a frequency of 25kHz, and then immersed in a 0.1 mol / L 2-hydroxyethylenediaminetetraacetic acid solution, 10 wt% triethoxysilane was added, heated to 45°C, and then magnetically stirred for 3 hours, filtered and dried to obtain modified nanographene; S1.2: NaBH4 and ethanol solution were mixed in a mass ratio of 1:45 and placed in an ice-water bath at 0°C, and then ultrasonicated for 10 minutes using an ultrasonic generator to obtain a NaBH4 solution. CuCl2, modified nanographene and ethanol solution were mixed in a mass ratio of 1:0.8:60 and placed in a container. After adding 0.5wt% polyvinyl pyrrolidone, nitrogen was continuously introduced for 10 minutes at a nitrogen flow rate of 40mL / min. Then, the mixture was placed in an ice-water bath at 0°C and ultrasonicated for 10 minutes. The sealed container was dripped through a catheter. 25wt% NaBH4 solution was added dropwise while being rapidly stirred. After the addition of the NaBH4 solution was completed, it was placed in an ice water bath at 0°C for 45 minutes, and then centrifuged at 10000rpm for 5 minutes. After filtering, it was immersed in an ethanol solution and stirred for 6 minutes. The above ethanol solutions were all mixed with ethanol and deionized water, and the volume fraction of ethanol was 50%. Then, centrifugal filtration was performed, and the mixture was repeated twice and then placed in a drying oven at 60°C for 4 hours to obtain copper-coated graphene nanoparticles. S1.3: The copper-coated graphene nanoparticles and oxygen-free pure copper powder are mixed evenly in a mass ratio of 1:10, loaded into a mold, and pressed into shape by cold isostatic pressing at 300 MPa. The mixture is then placed in a vacuum sintering furnace for sintering to obtain a graphene-copper ingot. The ingot is then subjected to horizontal continuous casting, annealing, milling to remove the oxide layer, rolling, and degreasing and cleaning to obtain a high thermal stability thermal conductive copper plate with a thickness of 0.5 mm.
[0021] S2: Pulsed laser deposition of CuO transition layer on ceramic substrate S2.1: Copper acetate and ethanol solution are mixed in a container at a mass ratio of 1:40, and sodium hydroxide is added dropwise while stirring to adjust the pH value of the solution to 10. The sealed container is shaken for 20 minutes, filtered, washed twice with deionized water and anhydrous ethanol in sequence, and then dried in a vacuum drying oven at 60°C for 6 hours to obtain CuO nanoparticles; S2.2: Rinse the ceramic substrate with deionized water for 2 times. The material of the ceramic substrate is Si3N4 ceramic. Then, immerse it in an acetone solution for ultrasonic cleaning for 15 minutes. Then, immerse it in a 5% hydrofluoric acid solution for ultrasonic cleaning for 5 minutes. Then, immerse it in deionized water for ultrasonic cleaning for 8 minutes. Then, put it in a drying oven and adjust the temperature to 100°C for drying for 10 minutes to obtain a clean ceramic substrate. S2.3: Oxygen is introduced into the gas chamber of the RF plasma generator. The gas chamber is equipped with an electrothermal nozzle, which is connected to the deposition chamber of the pulsed laser deposition system. First, the valve of the electrothermal nozzle is closed, and the power of the RF plasma generator is set to 300 W and the RF frequency is set to 13 MHz. At the same time, a clean ceramic substrate is used as a substrate, and CuO nanoparticles with a purity of more than 99% are used as a target material. The distance between the substrate and the target material is adjusted to 6 cm, and the pressure of the deposition chamber is pre-pumped to 1×10 -4 Pa and set the laser parameters to 180mJ / Plus and the laser density to 4J / cm 2 First, turn on the plasma generator to continuously generate oxygen plasma, then heat the electric heating nozzle to 400°C, the deposition chamber temperature to 500°C, and then open the electric heating nozzle valve, control the oxygen plasma flow rate to 15sccm, control the deposition frequency of the pulsed laser deposition system to 5Hz, and control the thickness of the deposited CuO film to 50μm to obtain a CuO transition layer coated ceramic substrate.
[0022] S3: Composite of high thermal stability thermal conductive copper plate and CuO transition layer ceramic substrate S3.1: The copper clad laminate is assembled in a sandwich structure of high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate. Quartz plates are used to clamp the upper and lower parts, and the pressure is adjusted to 5×10 -3 MPa, and a pre-assembled copper clad laminate is obtained; S3.2: Place the pre-assembled copper clad laminate in a vacuum furnace for brazing, and adjust the vacuum degree in the vacuum furnace to 10 -4 Pa, then firstly heat the temperature to 800°C at a heating rate of 5°C / min, keep the temperature for 25 minutes, then heat the temperature to 920°C at a heating rate of 2°C / min, and then cool to room temperature with the furnace to obtain a DBC ceramic copper clad laminate.
[0023] Example 2 A preparation process of a DBC ceramic copper-clad laminate, such as Figure 1 As shown, the following steps are included: S1: Preparation of high thermal stability thermal conductive copper plate S1.1: 3 portions of nanographene were immersed in a 60% fluorotitanic acid solution, and then ultrasonicated for 8 minutes using an ultrasonic generator at a frequency of 25 kHz, and then immersed in a 0.1 mol / L 2-hydroxyethylenediaminetetraacetic acid solution, 15 wt % of triethoxysilane was added, heated to 45° C., and then magnetically stirred for 3 hours, filtered and dried to obtain modified nanographene; S1.2: NaBH4 and ethanol solution were mixed in a mass ratio of 1:50 and placed in an ice-water bath at 0°C, and then ultrasonicated for 10 minutes using an ultrasonic generator to obtain a NaBH4 solution. CuCl2, modified nanographene and ethanol solution were mixed in a mass ratio of 1:1.2:80 and placed in a container. After adding 0.8wt% polyvinyl pyrrolidone, nitrogen was continuously introduced for 10 minutes at a nitrogen flow rate of 40mL / min. Then, the mixture was placed in an ice-water bath at 0°C and ultrasonicated for 10 minutes. The sealed container was dripped through a catheter. 30wt% NaBH4 solution was added dropwise while being rapidly stirred. After the addition of the NaBH4 solution was completed, it was placed in an ice water bath at 0°C for 45 minutes, and then centrifuged at 10000rpm for 5 minutes. After filtering, it was immersed in an ethanol solution and stirred for 6 minutes. The above ethanol solutions were all mixed with ethanol and deionized water, and the volume fraction of ethanol was 50%. Then, centrifugal filtration was performed, and the mixture was repeated twice and then placed in a drying oven at 60°C for 4 hours to obtain copper-coated graphene nanoparticles. S1.3: The copper-coated graphene nanoparticles and oxygen-free pure copper powder are mixed evenly in a mass ratio of 1:12, loaded into a mold, and pressed into shape by cold isostatic pressing at 300 MPa. The mixture is then placed in a vacuum sintering furnace for sintering to obtain a graphene-copper ingot. The ingot is then subjected to horizontal continuous casting, annealing, milling to remove the oxide layer, rolling, and degreasing and cleaning to obtain a high thermal stability thermal conductive copper plate with a thickness of 0.5 mm.
[0024] S2: Pulsed laser deposition of CuO transition layer on ceramic substrate S2.1: Copper acetate and ethanol solution are mixed in a container at a mass ratio of 1:50, and sodium hydroxide is added dropwise while stirring to adjust the pH value of the solution to 10. The sealed container is shaken for 20 minutes, filtered, washed twice with deionized water and anhydrous ethanol in sequence, and then dried in a vacuum drying oven at 60°C for 6 hours to obtain CuO nanoparticles; S2.2: Rinse the ceramic substrate with deionized water for 2 times. The material of the ceramic substrate is Si3N4 ceramic. Then, immerse it in an acetone solution for ultrasonic cleaning for 15 minutes. Then, immerse it in a 5% hydrofluoric acid solution for ultrasonic cleaning for 5 minutes. Then, immerse it in deionized water for ultrasonic cleaning for 8 minutes. Then, put it in a drying oven and adjust the temperature to 100°C for drying for 10 minutes to obtain a clean ceramic substrate. S2.3: Oxygen is introduced into the gas chamber of the RF plasma generator. The gas chamber is equipped with an electrothermal nozzle, which is connected to the deposition chamber of the pulsed laser deposition system. First, the valve of the electrothermal nozzle is closed, and the power of the RF plasma generator is set to 300 W and the RF frequency is set to 13 MHz. At the same time, a clean ceramic substrate is used as a substrate, and CuO nanoparticles with a purity of more than 99% are used as a target material. The distance between the substrate and the target material is adjusted to 6 cm, and the pressure of the deposition chamber is pre-pumped to 1×10 -4 Pa and set the laser parameters to 180mJ / Plus and the laser density to 4J / cm 2 First, turn on the plasma generator to continuously generate oxygen plasma, then heat the electric heating nozzle to 400°C, the deposition chamber temperature to 500°C, and then open the electric heating nozzle valve, control the oxygen plasma flow rate to 15sccm, control the deposition frequency of the pulsed laser deposition system to 5Hz, and control the thickness of the deposited CuO film to 50μm to obtain a CuO transition layer coated ceramic substrate.
[0025] S3: Composite of high thermal stability thermal conductive copper plate and CuO transition layer ceramic substrate S3.1: The copper clad laminate is assembled in a sandwich structure of high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate. Quartz plates are used to clamp the upper and lower parts, and the pressure is adjusted to 5×10 -3 MPa, and a pre-assembled copper clad laminate is obtained; S3.2: Place the pre-assembled copper clad laminate in a vacuum furnace for brazing, and adjust the vacuum degree in the vacuum furnace to 10 -4 Pa, then firstly heat the temperature to 800°C at a heating rate of 5°C / min, keep the temperature for 25 minutes, then heat the temperature to 920°C at a heating rate of 2°C / min, and then cool to room temperature with the furnace to obtain a DBC ceramic copper clad laminate.
[0026] Example 3 A preparation process of a DBC ceramic copper-clad laminate, such as Figure 1 As shown, the following steps are included: S1: Preparation of high thermal stability thermal conductive copper plate S1.1: 2 portions of nanographene were immersed in a 70% fluorotitanic acid solution, and then ultrasonicated for 10 minutes using an ultrasonic generator at a frequency of 30 kHz, and then immersed in a 0.2 mol / L 2-hydroxyethylenediaminetetraacetic acid solution, 10 wt % triethoxysilane was added, heated to 60° C., and then magnetically stirred for 4 hours, filtered and dried to obtain modified nanographene; S1.2: NaBH4 and ethanol solution were mixed in a mass ratio of 1:45 and placed in an ice-water bath at 4°C, and then ultrasonicated for 15 minutes using an ultrasonic generator to obtain a NaBH4 solution. CuCl2, modified nanographene and ethanol solution were mixed in a mass ratio of 1:0.8:60 and placed in a container. After adding 0.5wt% polyvinyl pyrrolidone, nitrogen was continuously introduced for 15 minutes at a nitrogen flow rate of 45mL / min. Then, the mixture was placed in an ice-water bath at 4°C and ultrasonicated for 15 minutes. The sealed container was dripped through a catheter. 25wt% NaBH4 solution was added dropwise while being rapidly stirred. After the addition of the NaBH4 solution was completed, it was placed in an ice water bath at 4°C for 60 minutes, and then centrifuged at 12000rpm for 6 minutes. After filtering, it was immersed in an ethanol solution and stirred for 8 minutes. The above ethanol solutions were all mixed with ethanol and deionized water, and the volume fraction of ethanol was 60%. Then, centrifugal filtration was performed, and the mixture was repeated 3 times and then placed in a drying oven at 65°C for 6 hours to obtain copper-coated graphene nanoparticles. S1.3: The copper-coated graphene nanoparticles and oxygen-free pure copper powder are mixed evenly in a mass ratio of 1:10, loaded into a mold, and pressed into shape by cold isostatic pressing at 500 MPa. The mixture is then placed in a vacuum sintering furnace for sintering to obtain a graphene-copper ingot. The ingot is then subjected to horizontal continuous casting, annealing, milling to remove the oxide layer, rolling, and degreasing and cleaning to obtain a 1 mm thick high thermal stability thermal conductive copper plate.
[0027] S2: Pulsed laser deposition of CuO transition layer on ceramic substrate S2.1: Copper acetate and ethanol solution were mixed in a mass ratio of 1:40 in a container, sodium hydroxide was added dropwise while stirring to adjust the pH value of the solution to 12, and then the sealed container was shaken for 30 minutes, filtered, washed with deionized water and anhydrous ethanol three times in sequence, and then dried in a vacuum drying oven at 65°C for 8 hours to obtain CuO nanoparticles; S2.2: Rinse the ceramic substrate with deionized water for 3 times. The material of the ceramic substrate is Si3N4 ceramic. Then, immerse it in an acetone solution for ultrasonic cleaning for 20 minutes. Then, immerse it in a 5% hydrofluoric acid solution for ultrasonic cleaning for 6 minutes. Then, immerse it in deionized water for ultrasonic cleaning for 10 minutes. Then, put it in a drying oven and adjust the temperature to 120°C for drying for 15 minutes to obtain a clean ceramic substrate. S2.3: Oxygen is introduced into the gas chamber of the RF plasma generator. The gas chamber is equipped with an electrothermal nozzle, which is connected to the deposition chamber of the pulsed laser deposition system. First, the valve of the electrothermal nozzle is closed, and the power of the RF plasma generator is set to 500 W and the RF frequency is set to 14 MHz. At the same time, a clean ceramic substrate is used as a substrate, and CuO nanoparticles with a purity of more than 99% are used as a target material. The distance between the substrate and the target material is adjusted to 8 cm, and the pressure of the deposition chamber is pre-pumped to 2×10 -4 Pa and set the laser parameters to 200mJ / Plus and the laser density to 5J / cm 2 First, turn on the plasma generator to continuously generate oxygen plasma, then heat the electric heating nozzle to 450°C, the deposition chamber temperature to 550°C, then open the electric heating nozzle valve, control the oxygen plasma flow rate to 20sccm, control the deposition frequency of the pulsed laser deposition system to 6Hz, and control the thickness of the deposited CuO film to 100μm to obtain a CuO transition layer coated ceramic substrate.
[0028] S3: Composite of high thermal stability thermal conductive copper plate and CuO transition layer ceramic substrate S3.1: The copper clad laminate is assembled in a sandwich structure of high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate. Quartz plates are used to clamp the upper and lower parts, and the pressure is adjusted to 7×10 -3 MPa, and a pre-assembled copper clad laminate is obtained; S3.2: Place the pre-assembled copper clad laminate in a vacuum furnace for brazing. Adjust the vacuum degree in the vacuum furnace to 5×10 -4 Pa, then firstly heat the temperature to 850°C at a heating rate of 6°C / min, keep the temperature for 30 minutes, then heat the temperature to 950°C at a heating rate of 3°C / min, and then cool to room temperature with the furnace to obtain a DBC ceramic copper clad laminate.
[0029] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that, in step S2.3, oxygen plasma is not introduced into the deposition chamber of the pulsed laser deposition system in Comparative Example 1, and the remaining steps are the same as those in Example 1. The prepared DBC ceramic copper clad laminate is recorded as Comparative Example 1.
[0030] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes step S1, replaces the subsequent high thermal stability thermal conductive copper plate with a 0.5 mm thick pure copper plate, and the remaining steps are the same as Example 1. The prepared DBC ceramic copper clad laminate is recorded as Comparative Example 2.
[0031] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes step S1.1, replaces the subsequent modified nano-graphene with nano-graphene, and the remaining steps are the same as those in Example 1. The prepared DBC ceramic copper-clad laminate is recorded as Comparative Example 3.
[0032] Experiment 1 The DBC ceramic copper-clad laminate prepared in the embodiment and comparative example 1 were taken respectively, and the peel strength of their copper clad layers was measured respectively using a Shimadzu tensile machine. The test was performed three times, and the data were recorded and tabulated, as shown in Table 1. It can be seen that the peel strength of the DBC ceramic copper-clad laminate prepared in the embodiment is better than that of comparative example 1, which can prove that the peel strength of the DBC ceramic copper-clad laminate can be improved by introducing oxygen plasma during the CuO pulsed laser deposition coating process on the clean ceramic substrate.
[0033] Table 1: Peel strength of DBC ceramic copper clad laminate
[0034] Experiment 2 The DBC ceramic copper-clad laminate prepared in the embodiment, comparative example 1 and comparative example 2 were cut into three disc-shaped samples with a diameter of 6 mm respectively, and their thermal conductivity was measured according to GB / T22588-2008 "Flash method for measuring thermal diffusion coefficient or thermal conductivity", the experimental temperature was 350±1K, and the data were recorded and tabulated, as shown in Table 2. It can be seen that the thermal conductivity of the DBC ceramic copper-clad laminate prepared in the embodiment is greater than that of comparative example 1 and comparative example 2, which can prove that the introduction of oxygen plasma in the process of CuO pulsed laser deposition coating on the clean ceramic substrate can improve the thermal conductivity of the DBC ceramic copper-clad laminate, and it can also be proved that the prepared high thermal stability thermal conductive copper plate can improve the thermal conductivity of the DBC ceramic copper-clad laminate.
[0035] Table 2: Thermal conductivity of DBC ceramic copper clad laminate
[0036] Experiment 3 Take two portions of DBC ceramic copper-clad laminates prepared in the embodiment, comparative example 2 and comparative example 3 respectively, and adopt a high and low temperature cycle number test method: set the temperature from -50°C to maintain for 15 minutes, then raise the temperature to 150°C, then maintain at 150°C for 15 minutes, cool to -50°C, and perform N cycles in sequence until the ceramic cracks or the copper layer peels off, record the number of cycles and make a table, as shown in Table 3, it can be seen that the number of high and low temperature cycles of the DBC ceramic copper-clad laminates prepared in the embodiment is greater than that of comparative examples 2 and 3, indicating that the thermal stability of the DBC ceramic copper-clad laminates prepared in the embodiment is better than that of comparative examples 2 and 3, which can prove that when polyvinyl pyrrolidone is added, the growth of a nano-copper layer on the surface of the modified nano-graphene can improve the thermal stability of the DBC ceramic copper-clad laminate, and it can be proved that modifying the nano-graphene can also improve the thermal stability of the DBC ceramic copper-clad laminate.
[0037] Table 3: High and low temperature cycle times of DBC ceramic copper clad laminate
[0038] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A preparation process of a DBC ceramic copper-clad laminate, characterized in that: The following steps are involved: S1: Preparation of high thermal stability thermal conductive copper plate The nanographene is immersed in a fluorotitanic acid solution for ultrasonic treatment, and then immersed in a 2-hydroxyethylenediaminetetraacetic acid solution, triethoxysilane is added, and the temperature is increased and magnetic stirring is performed, and the modified nanographene is obtained by filtration and drying, NaBH4 and ethanol solution are mixed and placed in an ice-water bath for ultrasonic treatment to obtain a NaBH4 solution, CuCl2, the modified nanographene and the ethanol solution are evenly mixed, and nitrogen is continuously introduced after polyvinyl pyrrolidone is added, and then the solution is placed in an ice-water bath for ultrasonic treatment, and the container is sealed and the NaBH4 solution is added dropwise while stirring, and the container is allowed to stand in an ice-water bath, and centrifugation, filtration and washing are repeated, and finally drying is obtained to obtain copper-coated graphene nanoparticles, and the copper-coated graphene nanoparticles are mixed with oxygen-free pure copper powder for cold isostatic pressing, and graphene-copper ingots are obtained after sintering, and then horizontal continuous casting, annealing, milling to remove the oxide layer, rolling and degreasing and cleaning are performed in sequence to obtain a high thermal stability thermal conductive copper plate; S2: Pulsed laser deposition of CuO transition layer on ceramic substrate The copper acetate and ethanol solution are mixed and placed in a container, the pH value of the solution is adjusted and the sealed container is shaken, after filtering, it is washed with deionized water and anhydrous ethanol in sequence, and dried to obtain CuO nanoparticles, after rinsing the ceramic substrate with deionized water, it is immersed in acetone solution, hydrofluoric acid solution and deionized water in sequence for ultrasonic cleaning, and dried to obtain a clean ceramic substrate, the clean ceramic substrate is used as a substrate, and the CuO nanoparticles are used as a target material and placed in a deposition chamber of a pulsed laser deposition system for deposition coating, and oxygen plasma is introduced into the deposition chamber through a heated electric heating nozzle while the coating is being deposited, so as to obtain a CuO transition layer-coated ceramic substrate; S3: Composite of high thermal stability thermal conductive copper plate and CuO transition layer ceramic substrate The copper clad laminate is assembled in a sandwich structure of a high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate, and is clamped by a quartz plate to obtain a pre-assembled copper clad laminate. The pre-assembled copper clad laminate is placed in a vacuum furnace for brazing, the vacuum degree in the vacuum furnace is adjusted, and then two-stage temperature rising brazing is performed. After cooling, a DBC ceramic copper clad laminate is obtained.
2. The preparation process of a DBC ceramic copper-clad laminate according to claim 1, characterized in that: Step S1: Preparation of a high thermal stability thermal conductive copper plate, comprising the following steps: S1.1: immerse 2-3 portions of nanographene in a 60-70% fluorotitanic acid solution, then perform ultrasonic treatment for 8-10 minutes at a frequency of 25-30kHz using an ultrasonic generator, then immerse in a 0.1-0.2 mol / L 2-hydroxyethylenediaminetetraacetic acid solution, add 10-15wt% triethoxysilane, heat to 45-60°C, then perform magnetic stirring for 3-4 hours, filter and dry to obtain modified nanographene; S1.2: NaBH4 and ethanol solution were mixed in a mass ratio of 1: (45-50) and placed in an ice water bath at 0-4°C, and then ultrasonicated for 10-15 minutes using an ultrasonic generator to obtain a NaBH4 solution. CuCl2, modified nanographene and ethanol solution were mixed in a mass ratio of 1: (0.8-1.2): (60-80) and placed in a container. 0.5-0.8wt% polyvinyl pyrrolidone was added and nitrogen was continuously introduced for 10-15 minutes, and then placed in an ice water bath at 0-4°C and ultrasonicated for 10-15 minutes. minutes, dripping 25-30wt% NaBH4 solution through a catheter in a sealed container, stirring rapidly while dripping, and after the NaBH4 solution is dripped, continue to stand in an ice water bath at 0-4°C for 45-50 minutes, and then centrifuge at a speed of 10000-12000rpm for 5-6 minutes, and then immerse in an ethanol solution and stir for 6-8 minutes after filtering, and then centrifuge and filter again, repeat 2-3 times, and then place in a drying oven at a temperature of 60-65°C for 4-6 hours to obtain copper-coated graphene nanoparticles; S1.3: The copper-coated graphene nanoparticles and oxygen-free pure copper powder are mixed evenly in a mass ratio of 1: (10-12), loaded into a mold, and pressed into shape by cold isostatic pressing at 300-500Mpa. The mixture is then placed in a vacuum sintering furnace for sintering to obtain a graphene-copper ingot. The ingot is then subjected to horizontal continuous casting, annealing, milling to remove the oxide layer, rolling, and degreasing and cleaning to obtain a thermally conductive copper plate with high thermal stability.
3. The preparation process of a DBC ceramic copper-clad laminate according to claim 1, characterized in that: Step S2: pulse laser deposition of CuO transition layer on ceramic substrate, including the following steps: S2.1: copper acetate and ethanol solution are mixed in a container at a mass ratio of 1: (40-50), the pH of the solution is adjusted to 10-12, and then the sealed container is shaken for 20-30 minutes, filtered, washed with deionized water and anhydrous ethanol 2-3 times in sequence, and then placed in a vacuum drying oven at a temperature of 60-65°C for 6-8 hours to obtain CuO nanoparticles; S2.2: Rinse the ceramic substrate with deionized water for 2-3 times, then immerse it in an acetone solution for ultrasonic cleaning for 15-20 minutes, then immerse it in a 5-6% hydrofluoric acid solution for ultrasonic cleaning for 5-6 minutes, then immerse it in deionized water for ultrasonic cleaning for 8-10 minutes, then put it in a drying oven, adjust the temperature to 100-120°C and dry it for 10-15 minutes to obtain a clean ceramic substrate; S2.3: Oxygen is introduced into the gas chamber of the RF plasma generator. The gas chamber is equipped with an electrothermal nozzle, which is connected to the deposition chamber of the pulsed laser deposition system. First, the electrothermal nozzle valve is closed, and the RF plasma generator power is set to 300-500W and the RF frequency is set to 13-14MHz. At the same time, a clean ceramic substrate is used as a substrate, and CuO nanoparticles with a purity of more than 99% are used as a target material. The distance between the substrate and the target material is adjusted to 6-8cm, and the pressure of the deposition chamber is pre-pumped to 1×10 -4 -2×10 -4 Pa and set the laser parameters to 180-200mJ / Plus and the laser density to 4-5J / cm 2 First, turn on the plasma generator to continuously generate oxygen plasma, then heat the electric heating nozzle to 400-450°C, the deposition chamber temperature to 500-550°C, then open the electric heating nozzle valve, control the oxygen plasma flow rate to 15-20sccm, control the deposition frequency of the pulsed laser deposition system to 5-6Hz, and control the thickness of the deposited CuO film to 50-100μm to obtain a CuO transition layer-coated ceramic substrate.
4. The preparation process of a DBC ceramic copper-clad laminate according to claim 1, characterized in that: Step S3: Compounding the high thermal stability thermal conductive copper plate with the CuO transition layer plated ceramic substrate, comprising the following steps: S3.1: The copper clad laminate is assembled in a sandwich structure of high thermal stability thermal conductive copper plate-CuO-plated transition layer ceramic substrate-high thermal stability thermal conductive copper plate. Quartz plates are used to clamp the upper and lower parts, and the pressure is adjusted to 5×10 -3 -7×10 -3 MPa, and a pre-assembled copper clad laminate is obtained; S3.2: Place the pre-assembled copper clad laminate in a vacuum furnace for brazing, and adjust the vacuum degree in the vacuum furnace to 10 -4 -5×10 -4 Pa, then heat it to 800-850°C at a heating rate of 5-6°C / min, keep it warm for 25-30 minutes, then heat it to 920-950°C at a heating rate of 2-3°C / min, and then cool it to room temperature with the furnace to obtain a DBC ceramic copper clad laminate.
5. The preparation process of a DBC ceramic copper-clad laminate according to claim 1, characterized in that: The ethanol solution in step S1.2 is a mixture of ethanol and deionized water, wherein the volume fraction of ethanol is 50-60%.
6. The preparation process of a DBC ceramic copper-clad laminate according to claim 2, characterized in that: The nitrogen gas flow rate in step S1.2 is 40-45 mL / min.
7. The preparation process of a DBC ceramic copper-clad laminate according to claim 3, characterized in that: The thickness of the high thermal stability thermal conductive copper plate prepared in step S1.3 is 0.5-1 mm.
8. The preparation process of a DBC ceramic copper-clad laminate according to claim 3, characterized in that: Step S2.1: The pH value is adjusted to 10-12 by adding sodium hydroxide dropwise while stirring.
9. The preparation process of a DBC ceramic copper-clad laminate according to claim 5, characterized in that: The material of the ceramic substrate in step S2.2 is Si3N4 ceramic.
10. A DBC ceramic copper-clad laminate, characterized in that: The DBC ceramic copper-clad plate is prepared by the preparation process of any one of claims 1 to 9.
Citation Information
Patent Citations
Amino-functionalization assembling method for graphene
CN103773086A
Preparation method of n type copper oxide thin film
CN105463373A
Method for improving critical current of YBCO thick film
CN105695940A
Preparation method of ceramic copper-clad plate
CN111885852A
Active metal brazing ceramic copper-clad plate and preparation method thereof
CN117812816A
Cited By
Method for preparing nitride film
CN122279478A
